2015
DOI: 10.1111/cas.12749
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of cancer stem cell‐like properties in non‐small cell lung cancer with acquired resistance to afatinib

Abstract: Afatinib is an irreversible epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor (TKI) that is known to be effective against the EGFR T790M variant, which accounts for half of the mechanisms of acquired resistance to reversible EGFR-TKIs. However, acquired resistance to afatinib was also observed in clinical use. Thus, elucidating and overcoming the mechanisms of resistance are important issues in the treatment of non-small cell lung cancer. In this study, we established various afatinib-resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 39 publications
6
76
0
1
Order By: Relevance
“…Recently, also acquisition of EGFR and MET inhibitor resistance was occasionally connected with ABCB1 overexpression and concerned afatinib and erlotinib as well as PHA-665752, respectively [39, 40]. In the case of afatinib and PHA-665752 resistance, upregulation of ABCB1 expression was connected with selection for a cancer stem cell phenotype and an epithelial-to-mesenchymal transition (EMT) switch [41]. In our study, however, selection of a DMS114 cell subclone with enhanced stemness during nintedanib selection seems unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, also acquisition of EGFR and MET inhibitor resistance was occasionally connected with ABCB1 overexpression and concerned afatinib and erlotinib as well as PHA-665752, respectively [39, 40]. In the case of afatinib and PHA-665752 resistance, upregulation of ABCB1 expression was connected with selection for a cancer stem cell phenotype and an epithelial-to-mesenchymal transition (EMT) switch [41]. In our study, however, selection of a DMS114 cell subclone with enhanced stemness during nintedanib selection seems unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…A number of diverse mechanisms have been shown to underlie the development of acquired resistance to EGFR‐TKIs in NSCLC, which makes it difficult to overcome the drug resistance to EGFR‐TKIs. Starting with the report of the appearance of a secondary EGFR T790M mutation in 2005, numerous resistance mechanisms have been reported by our group and others, such as MET amplification, activation of the mesenchymal‐epithelial transition factor/hepatocyte growth factor axis, induction of epithelial‐to‐mesenchymal transition (EMT), acquisition of stem cell properties, and transformation from NSCLC into small cell lung cancer . Recently, osimertinib, a third‐generation EGFR‐TKI, was developed to overcome the resistance associated with the EGFR T790M mutation, and is expected to play an important role in the treatment of advanced NSCLC .…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the efficacy of the combined therapy with MEK and PI3K inhibitors for NSCLC after TKI failure has not been fully elucidated. In this study, we examined the effect of MEK plus PI3K dual inhibition on the cell growth of NSCLC with acquired resistance to EGFR‐TKIs using experimentally established EGFR‐TKI‐resistant cell lines, and explored the therapeutic potential of MEK/PI3K dual blockade therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Kobayashi et al (29) reported that Oct-4, the putative stem cell marker, could induce gefitinib resistance by regulating the CSC properties in aNSCLC cell line with EGFR mutation, and the samples from patients with acquired resistance to TKIs manifested a high level of Oct-4 expression. Similarly, cells resistant to the second generation TKI afatinib manifested CSC phenotypes, including an enhanced ability of colony formation and proliferation, and increased level of ALDH1 and CD44 (30). So it was implied that resistance to TKI could partly arise from CSCs.…”
Section: Discussionmentioning
confidence: 99%